(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Thepresent investigation addresses itself to the exploration of the creativepotential of scheduled caste students based upon diverse socio-economicparameters and selected demographic variables. The study will be conducted bytaking primary data as a base. However it will be supplemented with theavailable secondary data .The details of the methodology to be adopted in thepresent study will be as under: